0006 The use of standardised client simulation to improve clinical reasoning in veterinary undergraduates. (2nd November 2015) - Vinten, Claire; Cobb, Kate; Freeman, Sarah; Mossop, Liz
Abstract : Background: Standardised patients are widely used in undergraduate medical education for a multitude of purposes, including clinical reasoning skill development. In veterinary education, standardised clients (SCs) are used extensively in communication skill training, but are not commonly used to achieve other learning outcomes. Methodology: A simulated client program focussing on clinical reasoning skill development has been designed and implemented into The University of Nottingham School of Veterinary Medicine and Science (UNSVMS) curriculum. During a clinical placement in a first opinion small animal practice, all final year students undertake three consecutive consultations with an SC. They are required to diagnose and treat the accompanying canine patient, and are debriefed on their decision making strategies afterwards. Each consultation is filmed for later analysis. The session is designed to mirror typical consultations faced by new graduates in a fully immersive setting. Results: The effect of SC simulation on clinical reasoning development is being evaluated in four ways: Comparison of skill levels demonstrated in each consultation (using the Lasater Clinical Judgement Rubric (LCJR)) Student self-assessment of clinical reasoning (using the LCJR) pre- and post-simulation Quantitative student survey feedback Qualitative student focus group discussions The study is ongoing but preliminary self-assessment, survey and focus group data suggest students' clinical reasoning skills improve as a result of the sessions. Potential impact: Standardised patient simulation could be utilised within veterinary curricula to develop clinical reasoning in students.